The Relationship Between Family Support in Diabetes Management and Self-Acceptance among Patients with Type 2 Diabetes Mellitus - Dyah Restuning Prihati; Heny Prasetyorini; Miya Susilawati (PT.Mantaya Idea Batara, 2026)
Background: Patients with type 2 diabetes mellitus (T2DM) who have low self-acceptance often develop negative perceptions of their abilities, which can hinder effective diabetes self-management. T2DM is a chronic metabolic disorder characterized by insulin resistance and progressive β-cell dysfunction and long-term complications that negatively affect patients' quality of life (QoL). This study aims to determine the relationship between family support and self-acceptance in patients with T2DM. Methods: A cross-sectional study design was used, involving 221 respondents from Community Health Centers under the jurisdiction of the Ketapang District Health Office. Data were collected using the Hensarling Diabetes Family Support Scale (HDFSS) and the Illness Acceptance Scale (AIS). Result: The results showed a significant value of p = 0.000 and a Spearman correlation coefficient of r = 0.546, indicating a moderate positive correlation. Conclusion: There is a significant relationship between family support in diabetes management and self-acceptance in patients with T2DM